FLORBETAPIR IMAGING IN CLINICAL PRACTICE: A RETROSPECTIVE STUDY OF 100 PATIENTS. Issue 12 (15th November 2016) - Carswell, Christopher; Muckle, Kirsty; Waldman, Adam; Win, Zarni; Malhotra, Paresh; Perry, Richard
Abstract : Amyloid-PET imaging detects amyloid-beta pathology early in the course of Alzheimer's disease (AD) with high sensitivity and specificity and can classify the underlying disease process in patients with cognitive impairment. Florbetapir (Amyvid) is an amyloid-binding PET ligand with a long half-life, suitable for clinical use outside of the trial setting. How Amyvid imaging affects patient investigation and management in the "real-world" arena is unknown. We retrospectively reviewed the clinical details, investigations and management of 100 consecutive patients imaged with Amyvid as part of their routine clinical investigation at the Imperial Cognitive Clinic (ICC) sine 2014. Amyvid was employed in patients with young onset dementia (42%), mild or subjective cognitive impairment (33%), or AD patients with an atypical course or equivocal investigations (26%). Amyvid confirmed clinical suspicion in 68%% of patients but caused a change in diagnosis in 32% and induced a change in management in 47%. Patients had significantly fewer investigations post-Amyvid and patients who presented to ICC at a time when Amyvid was available had significantly fewer investigations pre-Amyvid also. Amyvid imaging commonly confirms diagnostic suspicion when investigating dementia, but also directly influences management and enables clear pathological segregation whilst reducing the overall burden of investigations performed.